Pilots’ training backgrounds affecting the attribution of event causal factors and airline safety management - Chan, Wesley Tsz-Kin; Li, Wen-Chin; Braithwaite, Graham (Elsevier, 2025)
For safety management in diverse aviation operators, it is necessary to investigate how different cultural factors interact in flight operations. Whilst prior studies have evaluated between-group cultural differences, there remains a research gap on whether within-group subcultural differences challenge the assimilation of people into the safety culture of the wider group. Cultural differences in how causal factors are perceived in the context of systemic safety deficiencies can affect the implementation of safety management strategies. In the present study, pilots from airline-sponsored, self-funded, and ex-military initial training backgrounds were invited to categorise an identical set of aircraft accident causal factors using the Human Factors Analysis and Classification System (HFACS). Results from 121 participants found significant differences amongst the three groups in the attribution of human factors conditions to organisational-level and supervisory-level categories. Significant associations amongst HFACS categories also differed amongst the three professional groups, with a considerable number of same-level associations found between ‘Preconditions for Unsafe Acts’ at the same level. Familiarity with organizational cultures was considered to impact the perception of causal factors. The finding of same-level associations presents a new contribution to the theoretical basis of the HFACS taxonomy, calling for a conceptual change in the directionality of causal sequences. The results suggest that the direction of safety remedies for different parts of the organisation is dependent on perceived relevance, which differs amongst subcultural groups. Findings are relevant to industry, particularly international airlines with diverse employee subcultural groups, for the implementation of safety management systems.
Keywords: Safety management systems; Human factors analysis and classification system; Accident investigation; Safety culture; Flight operations; Pilot training; 3505 Human Resources and Industrial Relations; 35 Commerce, Management, Tourism and Services; Logistics & Transportation; 3509 Transportation, logistics and supply chains